Implementation of Artificial Intelligence in Digital Marketing Development: a Thematic Review and Practical Exploration - Aditya Nirwana; Sudarmiatin; Melany (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2023)
This study aims to synthesize a comprehensive view of the use of AI in each stage of a series of marketing campaigns, including the stages of planning, initiating the marketing concept, marketing design, implementation and monitoring, and evaluation. By using the Systematic Literature Review (SLR) method, this study will try to "summarize" the use of AI in every stage of marketing that is studied in existing scientific research. It was concluded that with a variety of AI tools, AI can be used to understand target audiences, personalize marketing content to make it relevant, help understand consumer behavior and preferences based on data and analysis. , formulate verbal and visual digital marketing content, and monitor and evaluate the performance of advertising campaigns effectively.